The 4-pyridonyl group as a multifunctional electron donor in 1,8-naphthalimide-based photoluminescent and mechanically interlocked coordination compounds - Schmitt, Wolfgang; Gunnlaugsson, Thorfinnur (My University, 2018)
A new ligand system incorporating the 4-pyridonyl group as a substituent in 1,8-naphthalimide compounds is presented, with the pyridone group acting as both an electron donor for the internal charge transfer (ICT) fluorescence process and as a metal binding moiety. After establishing the solution-state photophysical properties of the new pyridyl and carboxyphenyl derivatives L1 and HL2, respectively, we have prepared and characterised four crystalline d-block metal complexes containing the 4-(4-pyridonyl)-1,8-naphthalimide residue. Complex 1, a discrete mononuclear Ag(I) complex, and complexes 2 and 3, both one-dimensional Zn(II) coordination polymers, all exhibit striking photoluminescence in the crystalline phase, the nature of which can be related to the solid-state behaviour of the pyridone substituent. Complex 4, a permanently porous Cu(II) material, shows no photoluminescence, but instead reveals a rare and intriguing inclined 2D → 3D polyrotaxane architecture, an unusual class of mechanically interlocked network in which the particular coordination chemistry of the pyridone group facilitates alternating looped and linear structural features.
PUBLISHED
Keywords: mononuclear Ag(I) complex; new ligand system; 4-pyridonyl group